Ketidakpastian Hukum Penerapan Pajak Karbon Terhadap Investor Asing di Sektor Energi Non-EBT: Tinjauan dari Perspektif Hukum Investasi : Indonesia, 2021–2025 - Dwi Marlianto (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Legal uncertainty in the implementation of the carbon tax poses significant challenges to Indonesia’s investment climate, particularly in the non-renewable energy sector. This study aims to examine how the postponement of carbon tax implementation, despite the operation of carbon trading instruments, affects foreign investors’ expectations from the perspective of investment law. The research employs a normative juridical (dogmatic) approach combined with a light event study on major policy milestones between 2021 and 2023, including Presidential Regulation No. 98/2021, Ministerial Regulation of Energy and Mineral Resources No. 16/2022, OJK Regulation No. 14/2023, the launch of IDXCarbon, and the announcement of the carbon tax delay until 2025. The findings reveal varied market responses in fossil-based utility firms’ stocks and bonds, indicating the presence of an uncertainty premium. From a legal standpoint, the asymmetric configuration between delayed fiscal instruments and the ongoing non-fiscal instruments potentially undermines the principle of legal certainty under Investment Law No. 25/2007, while also raising risks related to Fair and Equitable Treatment (FET) and legitimate expectations. Nevertheless, the state’s right to regulate remains a crucial foundation for balancing investor protection with the imperative of energy transition. This study underscores the importance of policy consistency and transparency to maintain investment attractiveness and strengthen the legitimacy of Indonesia’s climate regulation.